2018
DOI: 10.3390/rs10020176
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Correction and 3D Integration of Long-Range Ground-Based Hyperspectral Imagery for Mineral Exploration of Vertical Outcrops

Abstract: Abstract:Recently, ground-based hyperspectral imaging has come to the fore, supporting the arduous task of mapping near-vertical, difficult-to-access geological outcrops. The application of outcrop sensing within a range of one to several hundred metres, including geometric corrections and integration with accurate terrestrial laser scanning models, is already developing rapidly. However, there are few studies dealing with ground-based imaging of distant targets (i.e., in the range of several kilometres) such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…Terrestrial imaging spectrometry for mapping of near vertical geological outcrops has been the topic of many studies in recent years [35][36][37][38]. This approach has been applied in the Arctic by scanning the vertical cliffs from an opposing location such as a neighboring mountain [48,60]. However, such approach is not always feasible where data are to be acquired on a routine operational basis to provide information on mineralogy as part of large-scale mapping operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terrestrial imaging spectrometry for mapping of near vertical geological outcrops has been the topic of many studies in recent years [35][36][37][38]. This approach has been applied in the Arctic by scanning the vertical cliffs from an opposing location such as a neighboring mountain [48,60]. However, such approach is not always feasible where data are to be acquired on a routine operational basis to provide information on mineralogy as part of large-scale mapping operations.…”
Section: Discussionmentioning
confidence: 99%
“…The aim is, therefore, not to provide the most accurate dataset but to allow the best data acquisition without penalizing the other exploration activities in a time and cost efficient manner. Detailed atmospheric/radiometric and topographic corrections are beyond the scope of this paper and will be discussed in a forthcoming paper [60].…”
Section: Pre-processing Of Hyperspectral Datamentioning
confidence: 99%
“…However, the set-up of commercially available sensors is relatively inflexible. Past research has shown that reflectance in the short and medium wave infrared bands is more useful for sediment classification, and that hyperspectral sensors can accurately map geological properties of rock, e.g., [51]. Recent studies have mounted hyperspectral cameras to drones for a range of purposes [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Aside vegetation, the VNIR spectral range can bring valuable information on other objects of the interest such as Fe 3+ -bearing minerals [20], alteration minerals [24], rare earths [6], organic component [25] and optically active water substances [26]. Because of a relatively unstable platform and extremely challenging acquisition geometries with respect to sun illumination, very minute corrections are required [27,28].We propose an integrated remote sensing approach utilizing all the different levels of data resolutions to address these challenges; from satellite-to aircraft-to RPAS-based. The multiscale and multisource data combination entails the full scope of available remote sensing imaging solutions from space-borne to RPAS-based sensors as well as a dedicated field campaign for training and validation of the algorithms.…”
mentioning
confidence: 99%
“…Aside vegetation, the VNIR spectral range can bring valuable information on other objects of the interest such as Fe 3+ -bearing minerals [20], alteration minerals [24], rare earths [6], organic component [25] and optically active water substances [26]. Because of a relatively unstable platform and extremely challenging acquisition geometries with respect to sun illumination, very minute corrections are required [27,28].…”
mentioning
confidence: 99%